2010
DOI: 10.1128/mcb.00396-10
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Carboxyl Hydrolase BAP1 Forms a Ternary Complex with YY1 and HCF-1 and Is a Critical Regulator of Gene Expression

Abstract: The candidate tumor suppressor BAP1 is a deubiquitinating enzyme (DUB) involved in the regulation of cell proliferation, although the molecular mechanisms governing its function remain poorly defined. BAP1 was recently shown to interact with and deubiquitinate the transcriptional regulator host cell factor 1 (HCF-1). Here we show that BAP1 assembles multiprotein complexes containing numerous transcription factors and cofactors, including HCF-1 and the transcription factor Yin Yang 1 (YY1). Through its coiled-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
270
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(287 citation statements)
references
References 74 publications
16
270
1
Order By: Relevance
“…We emphasize that BAP1 heterozygous clones also exhibit chromosomal defects and decreased HR-mediated sIgM reversion. These observations suggest that BAP1 dosage is critical, which may reflect the fact that all nuclear BAP1 is contained within multiprotein complexes (13). Indeed, BAP1 heterozygous mutations are found in human tumors (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We emphasize that BAP1 heterozygous clones also exhibit chromosomal defects and decreased HR-mediated sIgM reversion. These observations suggest that BAP1 dosage is critical, which may reflect the fact that all nuclear BAP1 is contained within multiprotein complexes (13). Indeed, BAP1 heterozygous mutations are found in human tumors (29).…”
Section: Discussionmentioning
confidence: 99%
“…BAP1 forms multiprotein complexes with several chromatin-associated proteins, notably the host cell factor 1 (HCF-1), and regulates transcription (13). The Drosophila BAP1, Calypso, was shown to deubiquitinate H2Aub (14).…”
mentioning
confidence: 99%
“…In fact, a study in human cells has shown that BAP1 activates YY1-regulated genes in a DUB-dependent manner (22). In addition, genome-wide gene expression analyses showed that many genes are up-or down-regulated by BAP1 knockdown or knockout, indicating that BAP1 can be a corepressor or coactivator (13,22,23 are needed to understand which genes are regulated by BAP1, how BAP1 is recruited to the target genes, and how BAP1 controls gene expression. In particular, assessing the role of DUB activity and the requirement of the interactions with coregulators such as HCF-1 are necessary to figure out the complex mechanism of gene regulation by BAP1.…”
mentioning
confidence: 99%
“…HCF-1 was initially identified as a human coactivator for immediate-early gene expression of herpes simplex virus (HSV) by forming a complex (VP16-induced complex, VIC) with the HSV protein VP16 and the cellular transcriptional regulator Oct-1 (1). HCF-1 regulates cell-cycle progression by mediating associations between DNA-binding transcription factors and chromatin modifying complexes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%